ASTRONOMICAL VERSES IN THE QUR'AN (ANALYSIS OF IBN ʿĀSYŪR'S THOUGHTS IN KITĀB AL-TAḤRĪR WA AL-TANWĪR) - Ahmad Irfai, Nur; Abdul Shomad, Bukhori; Septiawadi; Hasna Astuti, Adilah (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
This article analyzes Ibn ʿĀshūr's understanding of astronomical verses in his tafsir al-Taḥrīr wa al-Tanwīr. Indeed, the Qur'an contains scientific cues that encourage the Ummah’s development and progress in science and technology. The Qur'an mentions the heavens and the earth, the sun, the moon and its rotation, east and west, galaxies, stars and planets, the symptoms of day and night, dawn and dusk, darkness and light, the sea, rivers, springs, wind, thick clouds containing rain and thin clouds, lightning and rain. The subject of this study is described using thematic and historical approaches, and the research method is library research. The results indicate that Ibn ʿĀshūr uses a scientific approach to understand astronomical verses in the Qur'an, allowing the understanding of the relationship between natural phenomena and theological aspects of God's Power. His contribution to the science of contemporary exegesis is to encourage the study of scientific facts in interpreting the Quran and take lessons from the creation of the universe. Ibn ʿĀshūr emphasizes using other sciences to explore the meaning of the Quran while still following the rules of exegesis. This approach strengthens the theological dimension of exegesis and helps to facilitate understanding on the theological implications of glorifying the Power of God as the Creator and Ruler of the Universe.